2021
DOI: 10.3389/fped.2021.638432
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of STAT3 Signal Pathway Activation on Retinopathy of Prematurity

Abstract: Objective: To investigate the mechanism of activation of the signal transducer and activator of transcription 3 (STAT3) signal pathway in the process of retinopathy of prematurity (ROP).Methods: Sixty newborn Sprague-Dawley (SD) rats were randomly separated into the hyperoxia and air control groups (n = 30/in each group). The serum hepcidin level on 21 d was measured using the enzyme-linked immunosorbent assay (ELISA). The expression of HAMP and STAT3 protein in the liver was determined using reverse transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The same research group later revealed that VEGF-induced STAT3 activation blocked retinal angiogenesis by downregulating local expression of erythropoietin (EPO) in Müller cells during phase 1 of OIR [106]. Ren et al's investigation in a rodent model exposed to hyperoxia demonstrated that hyperoxia-induced STAT3 signaling enhances hepcidin expression-a key protein involved in iron balance-suggesting a potential compensatory mechanism to counteract iron overload linked to neoangiogenesis and proposing targeting molecules to regulate iron regulation [107].…”
Section: The Central Role Of Nitro-oxidative Stress and Inflammatory ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The same research group later revealed that VEGF-induced STAT3 activation blocked retinal angiogenesis by downregulating local expression of erythropoietin (EPO) in Müller cells during phase 1 of OIR [106]. Ren et al's investigation in a rodent model exposed to hyperoxia demonstrated that hyperoxia-induced STAT3 signaling enhances hepcidin expression-a key protein involved in iron balance-suggesting a potential compensatory mechanism to counteract iron overload linked to neoangiogenesis and proposing targeting molecules to regulate iron regulation [107].…”
Section: The Central Role Of Nitro-oxidative Stress and Inflammatory ...mentioning
confidence: 99%
“…They emphasized its crucial function in negatively controlling JAK2/STAT3/VEGF-related angiogenesis, highlighting that its upregulation suppresses neoangiogenesis in the retinas of OIR mice [181]. Ren and colleagues, in a rodent model of ROP, demonstrated that S3I-201, a STAT3 pathway inhibitor, downregulated the expression of STAT3 and VEGF mRNA levels, effectively countering neoangiogenesis in ROP [107]. In another investigation, the E3 ubiquitin ligase synoviolin (SYVN1) was examined for its potential in ROP management.…”
Section: Targeting the Stat3 Signaling Pathway In Rop Managementmentioning
confidence: 99%
“…Likewise, deletion of STAT3 increased lung injury and alveolar capillary leak in mice exposed to hyperoxia (Hokuto et al 2004 ). However, STAT3 activation in hyperoxic rats has also been linked to the pathogenesis of retinopathy of prematurity (Byfield et al 2009 ; Ren et al 2021 ).…”
Section: Hyperoxia Directly and Indirectly Modulates Diverse Signalin...mentioning
confidence: 99%